Medication therapy management a comprehensive approach - Whalen, Karen
The need to improve the use of medications has major implications for the nation's healthcare system. Burdened by high costs and an ineffective process of providing medication therapy, the current prescription drug environment poses considerable risks to patient safety. Medication Therapy Managment (MTM) is designed to address these deficiencies--and this essential text gives pharmacists all the right MTM tools to identify and eliminate drug-related problems that can cause potentially severe adverse events. Cohesively organized, this expert-authored guide begins with an introduction to data sets for MTM, covering essential topics such as establishing quality and performance improvement, the payer perspective, conducting the comprehensive medication review, and reimbursement. The second part reviews MTM data sets for a wide spectrum of disorders, from asthma and atrial fibrillation to HIV and heart disease. Enhanced by the latest perspectives on therapeutics, including completely up-to-date tables throughout, Medication Therapy Management is a practical, skill-building roadmap for optimizing drug therapy and enhancing patient outcomes.